Analisis Penggunaan, Problematika dan Dampak Pemanfaatan Interactive Flat Panel (IFP) di Sekolah Dasar - Siti Khasanah Maisaroh; Faizatul Sundusiyyah; Nadia Salfa Taftazana; Telly Anisa Nurfadilla; Taufik Muhtarom (STKIP Subang, 2026)
This research aims to examine the patterns of utilization, challenges, and effects of Interactive Flat Panel (IFP) in elementary school instruction. It adopts a systematic literature review (SLR) method, reviewing seven journal articles published from 2016 to 2026, chosen based on topical alignment, full-text access, and relevance to elementary education. The results indicate that IFP is employed structuredly via multimedia content presentation, touchscreen functionalities (touch writing, drag and drop), interactive quizzes, and gamification tools like Wordwall and Quizizz. Identified challenges encompass teachers' insufficient digital and pedagogical skills, technical apprehension in device operation, unreliable internet connectivity, and inadequate incorporation of IFP into teaching strategies. Nonetheless, the overall effects of IFP use are positive, marked by enhanced student motivation, active engagement, collaboration, and better grasp of abstract concepts, alongside promoting interactive and student-centered learning. IFP's success hinges not merely on device availability, but also on organized management, ongoing teacher training, and robust infrastructure plus a collaborative school culture.